2021
DOI: 10.1101/2021.12.14.21267418
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 vaccination and Guillain-Barré syndrome: analyses using the National Immunoglobulin Database

Abstract: Vaccination against viruses has rarely been associated with Guillain-Barré syndrome (GBS). An association with the COVID-19 vaccine is unknown. We performed a population-based study of National Health Service (NHS) data in England and a multicentre surveillance study from UK hospitals, to investigate the relationship between COVID-19 vaccination and GBS.Firstly, we present a retrospective analysis of every GBS patient in England in the National Immunoglobulin Database (NID) linked with their COVID-19 vaccinati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…However, a study in the United Kingdom did not find a significant difference in presence of unilateral or bilateral facial weakness between those with GBS onset in the 42 days after COVID-19 vaccination (majority first doses of ChAdOx1) and those with GBS onset more than 42 days after COVID-19 vaccination or those with GBS onset during the same period that were not vaccinated. 22 More research is needed to determine if the presentation of GBS after adenoviral vector vaccine differs from GBS after other exposures such Abbreviations: BL, Brighton level; GBS, Guillain-Barré syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study in the United Kingdom did not find a significant difference in presence of unilateral or bilateral facial weakness between those with GBS onset in the 42 days after COVID-19 vaccination (majority first doses of ChAdOx1) and those with GBS onset more than 42 days after COVID-19 vaccination or those with GBS onset during the same period that were not vaccinated. 22 More research is needed to determine if the presentation of GBS after adenoviral vector vaccine differs from GBS after other exposures such Abbreviations: BL, Brighton level; GBS, Guillain-Barré syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, adverse events that occurred are rare. The incidence of Guillain Barré syndrome (GBS) as an example is 5.8 per million doses of Pfizer, AstraZeneca or Moderna compared [18] to 479 per million COVID-19 positive cases [19]. Similarly, thrombotic events of 3.83 cases per million doses [20] of J&J versus 0.08% of COVID-19 positive patients equate to 80,000 per million [21].…”
Section: Discussionmentioning
confidence: 99%
“…81 107 A recent analysis of the United Kingdom's National Health Service database found that the first dose of AZD1222 is associated with a risk of approximately 5.8 cases per million doses, while the first dose of BNT162b2 showed no excess risk. 109 Similarly, acute transverse myelitis has been reported in association with the AZD1222, Ad26.COV2.S, mRNA-12273, and CoronaVac vaccines. 84 85 86 87 88 89 Time of onset varies from 3 hours to 39 days.…”
Section: Adverse Effectsmentioning
confidence: 91%